Association of Fluid Accumulation with Clinical Outcomes in Critically Ill Children with Severe Sepsis - Chen, Jiao (PLoS One, 2016)
OBJECTIVE: To evaluate whether early and acquired daily fluid overload (FO), as well as fluctuations in fluid accumulation, were associated with adverse outcomes in critically ill children with severe sepsis. METHODS: This study enrolled 202 children in a pediatric intensive care unit (PICU) with severe sepsis. Early fluid overload was defined as ≥5% fluid accumulation occurring in the first 24 hours of PICU admission. The maximum daily fluid accumulation ≥5% occurring during the next 6 days in patients with at least 48 hours of PICU stay was defined as PICU-acquired daily fluid overload. The fluctuation in fluid accumulation was calculated as the difference between the maximum and the minimum daily fluid accumulation obtained during the first 7 days after admission. RESULTS: Of the 202 patients, 61 (30.2%) died during PICU stay. Among all patients, 41 (20.3%) experienced early fluid overload, including 9 with a FO ≥10%. Among patients with at least 48 hours of PICU stay (n = 154), 36 (23.4%) developed PICU-acquired daily fluid overload, including 2 with a FO ≥10%. Both early fluid overload (AOR = 1.20; 95% CI 1.08–1.33; P = 0.001; n = 202) and PICU-acquired daily fluid overload (AOR = 5.47 per log increase; 95% CI 1.15–25.96; P = 0.032; n = 154) were independent risk factors associated with mortality after adjusting for age, illness severity, etc. However, fluctuations in fluid accumulation were not associated with mortality after adjustment. Length of PICU stay increased with greater fluctuations in fluid accumulation in all patients with at least 48 hours of PICU stay (FO <5%, 5%-10% vs. ≥10%: 4 [3–8], 7 [4–11] vs. 10 [6–16] days; P <0.001; n = 154) and in survivors (4 [3–8], 7 [5–11] vs. 10 [5–15] days; P <0.001; n = 121). Early fluid overload achieved an area under-the-receiver-operating-characteristic curve of 0.74 (95% CI 0.65–0.82; P <0.001; n = 202) for predicting mortality in patients with severe sepsis, with a sensitivity of 67.2% and a specificity of 80.1% at the optimal cut-off value of 2.65%. CONCLUSIONS: Both early and acquired daily fluid overload were independently associated with PICU mortality in children with severe sepsis.